The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fpsyg.2014.00963
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ensemble interdependence in a string quartet through analysis of multidimensional performance data

Abstract: In a musical ensemble such as a string quartet, the musicians interact and influence each other's actions in several aspects of the performance simultaneously in order to achieve a common aesthetic goal. In this article, we present and evaluate a computational approach for measuring the degree to which these interactions exist in a given performance. We recorded a number of string quartet exercises under two experimental conditions (solo and ensemble), acquiring both audio and bowing motion data. Numerical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The authors suggested that the introduction of extreme unexpected dynamical changes in a well-rehearsed piece is a very unusual scenario for professional musicians, leading to a disruption of the normal sensorimotor communication patterns. Papiotis et al [65] analysed the audio and motion capture recordings (movement of the bow) of a quartet playing exercises under two experimental conditions: solo (i.e. each musician performs her part alone using a stripped-down version of the score) and ensemble.…”
Section: Social Interaction In Small Ensemblesmentioning
confidence: 99%
“…The authors suggested that the introduction of extreme unexpected dynamical changes in a well-rehearsed piece is a very unusual scenario for professional musicians, leading to a disruption of the normal sensorimotor communication patterns. Papiotis et al [65] analysed the audio and motion capture recordings (movement of the bow) of a quartet playing exercises under two experimental conditions: solo (i.e. each musician performs her part alone using a stripped-down version of the score) and ensemble.…”
Section: Social Interaction In Small Ensemblesmentioning
confidence: 99%
“…Musicians played in an anechoic chamber, and, in order to be synchronous with the rest of the instruments, they followed a video featuring a conductor and a pianist playing each of the four pieces. Note that the benefits of having isolated recordings comes at the expense of ignoring the interactions between musicians which commonly affect intonation and time-synchronization [37].…”
Section: Materials and Evaluationmentioning
confidence: 99%
“…However, this measure is not sensitive to the direction of information flow between agents and may result in type I errors if time series are autocorrelated (45). A few previous observational studies on music ensembles used Granger causality to analyze bow movements, timbre variations, and body sway of performers (39,46,47). However, because these studies did not manipulate leadership assignment or visual information, it remains unclear whether previous findings reflect a motor byproduct of executing music scores or are related to higher order aspects of joint action, such as leader-follower communication.…”
Section: Significancementioning
confidence: 99%